Eksistensi Nilai Sosial Budaya A’dengkapada dalam Acara Perkawinan Masyarakat Kelara Kabupaten Jeneponto - Hidayah Quraisy; Sitti Asnaeni (Equilibrium: Jurnal Pendidikan, 2017)
Research on the existence of socio-cultural value a'dengkapada in the marriage event Kelara people Jeneponto Regency. This study aims to determine the existence and cultural values a'dengkapada in the marriage. The type of this research is descriptive qualitative method, data collection is used by observation, in-depth interview, documentation technique from result of photo and archives of local government. The results showed that, the existence of A'dengkap culture in marriage event still survive until now in Kelara society of Jeneponto Regency. The social values contained in the A'dengkapada culture are (1) As a tradition passed down from generation to generation, (2) Gratitude to the creator after the rice harvest and as a plea to be given safety in marriage and appeal (3) Entertainment for families and relatives in the afternoon (4) distant family gatherings (5) containers improve mutual cooperation and togetherness among families and relatives before carrying out the A'dengkapada event.Keywords: Existence, Social Value, Culture, A'dengkapada